Current status of the small-scale fisheries and its resources at Peukan Bada coastal area in Aceh Province, Indonesia. Issue 1 (November 2021) - Haridhi, H A; Agustina, S; Damora, A; Fajri, I
Abstract: The coastal region around the world is in response to the significant change from the environment impacted by natural and anthropogenic sources. Such significant change could be observed in the coastal region where it had been experienced a natural disaster, climate change, and social-economic shift locally and regionally. The Peukan Bada coastal area in Aceh Province has experienced all of these features; thus, studying this region will give a new perspective and highlight the status of the small-scale fisheries and their governing marine-fisheries resources. In this study, we conducted the Rapid Appraisal of Fisheries Management System (RAFMS) to estimate the fisheries resources and their biological and physical attributes, market pattern, and main coastal problem facing by the community. The study found that the rapid and significant change of the fisheries resources and their biological and physical attributes as a result of a major natural disaster such as 26 December 2004 mega earthquake and tsunami, meanwhile a minor change to the market pattern was found changed in response to market demand, and major coastal problems are dominantly related to the community activities (anthropogenic) rather than resulted from natural event.